Microtia: A Combined Approach by Genetics and Audiology - Elham El-Saiid (The Egyptian Journal of Otolaryngology, 2016)
En Abstract Introduction Microtia is a condition in which the external portion of the ear (the auricle) is malformed. In the strictest definition, there is also narrowing or absence of the external auditory canal (external auditory meatus). Microtia varies in severity from barely discernible to an external ear with major structural changes. Hearing loss is a common feature that can be associated with microtia. There are different types of hearing loss–conductive, sensorineural, or mixed–depending on which part of the ear is not working as it should. Objectives The present study was designed with the following aims: (i) identification of the genetic etiology and patterns of inheritance of microtia for proper genetic counseling; (ii) early detection and identification of associated hearing impairment for proper management including use of a hearing aid and surgical intervention. Patients and methods Twenty children with microtia ranging in age between 1 and 15 years (mean: 6.2 ± 3.68 years) irrespective of sex were included in this study: 14 males and six females. All children were subjected to a full assessment of medical history, a general examination, an ENT examination, tympanometry, pure tone audiometry, and an auditory steady-state response test for patients not responding to a conventional audiometric test. Karyotyping, fluorescence in-situ hybridization (FISH) for Treacher Collins cases, radiological investigations, and fundus examination were also performed. Results Syndromic microtia was more frequent than nonsyndromic microtia. Treacher Collins syndrome was the most clinically diagnosed syndrome, followed by Goldenhar’s syndrome. There was one case of Down’s syndrome and another single case of Johnson–McMillin syndrome. Meatal atresia and preauricular tags were frequently present in the microtia cases, whereas middle ear and inner ear anomalies were only found in some cases. The most common presenting symptom of microtia is hearing loss. Its degree and type differ according to the severity of the disease and frequencies affected. In total, 88.5% (23 ears) have conductive hearing loss and 11.5% (three ears) have mixed hearing loss. Karyotyping was performed for 10 cases; nine cases were normal, whereas one case was abnormal (47XY, +21) (Down’s syndrome), which represents 5% of all cases studied. FISH was performed for four cases of Treacher Collins syndrome using a probe for chromosome 5 with gene map locus 5q31q33, but no deletion was found in the chromosome 5 Treacher Collins–Franceschetti 1 (TCOF1) gene. Conclusion Genetic predisposition for both autosomal dominant and autosomal recessive inheritance seems to be a strong determinant factor in the etiology of microtia than the environmental one. As for Treacher Collins, which is the most frequently clinically diagnosed syndrome in the current study, the FISH study showed that the 5q31-q33 locus may not carry the causative mutation as no single case was positive for this locus. Hearing impairment, of the conductive type, is the most frequent symptom that leads parents to seek medical advice and genetic counseling.